Differences in Inpatient Outcomes After Surgical Aortic Valve Replacement at Transcatheter Aortic Valve Replacement (TAVR) and Non‐TAVR Centers. Issue 22 (19th November 2019) - Jack, Godly; Arora, Sameer; Strassle, Paula D.; Sitammagari, Kranthi; Gangani, Kishorbhai; Yeung, Michael; Cavender, Matthew A.; O'Gara, Patrick T.; Vavalle, John P.
Abstract : Background: Transcatheter aortic valve replacement (TAVR) has solidified the importance of a heart team and revolutionized patient selection for surgical aortic valve replacement (SAVR). It is unknown if hospital ability to offer TAVR impacts SAVR outcomes. We investigated outcomes after SAVR between TAVR and non‐TAVR centers. Methods and Results: Hospitalizations of patients aged ≥50 years, undergoing elective SAVR between January 2012 and September 2015, in the National Readmission Database (NRD) were included. Multivariable logistic, linear, and generalized logistic regression models were used to adjust for patient and hospital characteristics and estimate association between undergoing SAVR at a TAVR center, compared with a non‐TAVR center. The association between TAVR volumes and these outcomes were also assessed. SAVR hospitalizations (n = 32 198) were identified; 22 066 (69%) at TAVR and 10 132 (31%) at non‐TAVR centers. SAVRs at TAVR centers had lower odds of inpatient mortality (odds ratio 0.67, 95% CI 0.55–0.82) and discharge to skilled nursing facility (odds ratio 0.92, 95% CI 0.85–0.99), compared with non‐TAVR centers. There was no difference in LOS (change in estimate −0.09, 95% CI −0.26 to 0.08) or 30‐day re‐admission (odds ratio 0.95, 95% CI 0.88–1.03). SAVRs performed at the highest TAVR volume centers had the lowest inpatient mortality, compared with non‐TAVR centers (odds ratio 0.43 95% CI 0.29–0.63). Conclusions: Patients undergoing SAVR at TAVR centers are more likely to survive and have better discharge disposition than patients undergoing SAVR at non‐TAVR centers. Whether this represents benefits of a heart‐team approach to care or differences in patient selection for SAVR when TAVR is unavailable requires further study.